Cilji in instrumenti zemljiške politike ter rast in razvoj mest - Šubic Kovač, Maruška (Urbani izziv, 2001)
Instruments of land policies are tied to its goals, as well as defined relations on property and law as set in the Constitution. Since these relations have changed in Slovenia, the instruments of land policy also have to change. When devising particular instruments basic principles have to be respected that are th estarting point for particular procedures. Only adequate legally defined instruments of land policies can be implemented in practice and affect the growth and development of cities in Slovenia.
Keywords: mesta; urbani razvoj; urbanism; urbanizem; zemljišča; zemljiška politika